FILSAFAT IBNU RUSYD HUBUNGAN AKAL DENGAN WAHYU - Kaipal Wahyudi (LPPM IAI Almuslim Aceh, 2023)
Ibnu Rushd was an intellectual Muslim who was known as a rational figure in the Islamic tradition. In his understanding he emphasized the importance of reason and logic in understanding religion and that all aspects of religion must be resolved through the power of reason. Ibn Rushd's famous work,